Prediksi Volume Impor Beras Nasional menggunakan Metode Support Vector Regression (SVR) - Cindy Inka Sari; Budi Darma Setiawan; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In Indonesia domestic rice production and rice imports are needed in order to attain national rice consumption. As the number of people increases and imported rice are consumed continuously, therefore Indonesia depends on rice imports from other countries. Prediction is needed to control the volume of national rice imports because excessive imports will cause negative losses and impacts. Support Vector Regression (SVR) is used to predict the volume of national rice imports. The data used in the prediction are data on consumption, production, volume of rice imports 1 year earlier as bebas variables and data on the volume of national rice imports in the period 1971 - 2016 as terikat variables. Tests carried out using 9 test data obtained the best parameters Sigma (Ïƒ) = 0.07, Lambda (Î») = 0.4, Constanta Learning Rate (cLr) = 0.01, Kompleksitas (C) = 10, Epsilon (Îµ) = 0.0004, the number of Iterations = 2000 and the number of training data = 37. The evaluation results were measured using Mean Absolute Presentage Error (MAPE). The best MAPE value produced is included in the sufficient category of 32.2748